2005
DOI: 10.1243/095440605x31409
|View full text |Cite
|
Sign up to set email alerts
|

SEWHAPM: Development of a Water Hydraulic Axial Piston Motor for Underwater Tool Systems

Abstract: Water hydraulic motor (WHM) is an important transmission component in a water hydraulic system. Because of different physicochemical properties of raw water when compared with mineral oil, the design for the WHM would be different from that for a mineral oil one. A static equilibrium-type water hydraulic axial piston motor (SEWHAPM), which is equipped with a global-moment-balanced plate valve and a hydrostatic slipper bearing with a concentric gap damper, is developed in this research. The mechanism of the glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…The suction, pressure, return, and bypass filters would be replaced every 15, 60, 6, and 24 days, respectively. The solution of optimistic extreme with most of |λ ± i |(i = 1, 2, 3, 4, 5, 6,7,8,9) being close to 0 demonstrated that a high satisfaction degree for both minimized system cost and maximized system reliability could be achieved under those advantageous conditions. The replacement periods of filters were mainly associated with the contaminant ingression/generation rates and the contaminant holding capability of filters.…”
Section: Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The suction, pressure, return, and bypass filters would be replaced every 15, 60, 6, and 24 days, respectively. The solution of optimistic extreme with most of |λ ± i |(i = 1, 2, 3, 4, 5, 6,7,8,9) being close to 0 demonstrated that a high satisfaction degree for both minimized system cost and maximized system reliability could be achieved under those advantageous conditions. The replacement periods of filters were mainly associated with the contaminant ingression/generation rates and the contaminant holding capability of filters.…”
Section: Results Analysismentioning
confidence: 99%
“…Combining equations (4b), (6), and 8, the expression of the contaminant ingression/generation rates can be obtained as…”
Section: Fig 1 Fps With a Bypass Filtration Systemmentioning
confidence: 99%
“…Characterization, methodology, and design Statement of problem As physicochemical properties of water are significantly different from those of mineral oil and other fluids, those issues should be considered in developing water hydraulic pumps. 13 First, the low viscosity of water can increase difficulty in forming hydrodynamic lubrication films between sliding bearing frictional pairs, and the insignificant responses of viscosity variations with water pressure do not result in EHL. Second, the low viscosity is associated with the poor lubricity of water, which means that the corrosive wear and erosion of water hydraulic components occurs easily.…”
Section: Introductionmentioning
confidence: 99%
“…However, WHM works with high-pressure and high-speed owing to the high pv values of friction pairs and the severe wear subject to the repeated alternating loads. 4,5 Bhushan and Gray 6 investigated several material combinations under high load and speed in synthetic seawater. They reported that the pv values of friction pairs in an axial piston motor were each one-third of those in a vane motor and one-tenth of those in a gear motor when the friction pairs adopted an identical material combination.…”
Section: Introductionmentioning
confidence: 99%